2005
DOI: 10.1002/cncr.21463
|View full text |Cite
|
Sign up to set email alerts
|

Race modifies the association between breast carcinoma pathologic prognostic indicators and the positive status for HER‐2/neu

Abstract: BACKGROUNDInferences about the variations in the biology of breast carcinoma between African‐Americans and Caucasians have been reported. The difference in the prevalence of positive HER‐2/neu breast carcinoma was evaluated and the race‐specific risk was assessed for positive HER‐2/neu among a cohort of women diagnosed with their first primary breast carcinoma, given the accepted prognostic pathologic indicators for positive HER‐2/neu status.METHODSDemographic, clinical, and pathologic data were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Despite missing information, our finding of a lack of significant difference in HER2 positivity between black and white patients is corroborated by several earlier reports. 1,7,12,33,34,43 HER2 positivity in our study (IHC 2+ scores deemed either positive or negative) falls within the range of recent reports estimating prevalence to be 12% to 25% of sampled tumors, 12,4346 which is a narrowing from initial estimates that ranged up to 40%. It is likely that early studies overestimated prevalence because these investigations tended to be composed of high-risk cohorts or proportionally more patients with regional or metastatic disease.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Despite missing information, our finding of a lack of significant difference in HER2 positivity between black and white patients is corroborated by several earlier reports. 1,7,12,33,34,43 HER2 positivity in our study (IHC 2+ scores deemed either positive or negative) falls within the range of recent reports estimating prevalence to be 12% to 25% of sampled tumors, 12,4346 which is a narrowing from initial estimates that ranged up to 40%. It is likely that early studies overestimated prevalence because these investigations tended to be composed of high-risk cohorts or proportionally more patients with regional or metastatic disease.…”
Section: Discussionsupporting
confidence: 81%
“…Our findings also are similar to previous reports that tumors from black patients with breast cancer tend to have significantly reduced ER or PR expression, 31,32 whereas HER2 status does not appear to vary by race. 7,33,34 Our findings suggest that divergent histologic distribution by race may underlie the disparity in TN status. Although the medullary subtype is relatively rare, we found that blacks had an almost 9-fold greater rate than that of white patients (3.3% vs. 0.40%), which is consistent with several earlier reports.…”
Section: Discussionmentioning
confidence: 67%
“…and Carey et al . found no significant difference in the prevalence of HER-2 tumors between African-American and white women (7, 12). However, Stark found grade and stage were associated with HER-2 status in whites but not in African-Americans (7).…”
Section: Discussionmentioning
confidence: 83%
“…Stark et al reported that whereas the risk of a positive HER2 status increased linearly with nuclear grade in Caucasian women, no correlation was seen among African American women [26]. HER2 expression may be dissociated from tumor grade in other patient groups as well.…”
Section: Discussionmentioning
confidence: 95%